1995
DOI: 10.3758/bf03206792
|View full text |Cite
|
Sign up to set email alerts
|

The perception of color from motion

Abstract: Weintroduce and explore a color phenomenon which requires the prior perception of motion to produce a spread of color over a region defined by motion. Wecall this motion-induced spread of color dynamic color spreading. The perception of dynamic color spreading is yoked to the perception of apparent motion: As the ratings of perceived motion increase, the ratings of color spreading increase. The effect is most pronounced if the region defined by motion is near 1 0 of visual angle. As the luminance contrast betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
66
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 53 publications
(49 reference statements)
0
66
0
Order By: Relevance
“…For high luminance levels of the background, observers reported seeing a disk moving over the field of dots and the spread of a desaturated color throughout this disk (Cicerone et al 1995). Under a range of low-luminance backgrounds the observers reported seeing a highly saturated, solidly colored green disk moving in front of a solid red field.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…For high luminance levels of the background, observers reported seeing a disk moving over the field of dots and the spread of a desaturated color throughout this disk (Cicerone et al 1995). Under a range of low-luminance backgrounds the observers reported seeing a highly saturated, solidly colored green disk moving in front of a solid red field.…”
Section: Resultsmentioning
confidence: 96%
“…Experimental evidence suggests that the receptive fields subserving the effect may be reasonably large. Cicerone et al (1995) showed that test regions near l deg (over a range of 0.3 to 2.4 deg) produce optimal color spread from motion. Although these sizes are too large to be compatible with the receptive field sizes of color-coded P ganglion cells of the primate retina, size alone does not allow us to specify where in the postretinaJ motion-processing chain the color spreading might occur.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations